Peningkatan Hasil Belajar Matematika melalui Penerapan Model Pembelajaran Kooperatif Tipe STAD berbantuan Media ULTRASI Pada Siswa Sekolah Dasar - Tangkearung, Sefrin Siang; Hendrik; Tulak, Topanus; Rara, Qlaludya Dwi (Elementary Journal : Jurnal Pendidikan Guru Sekolah Dasar, 2025)
This study aims to describe the improvement of students' mathematics learning outcomes by implementing the STAD type cooperative learning model assisted by ULTRASI media in grade IV students of UPT SDN 3 Sesean. The subjects in this study were 10 grade III students, 5 of whom were male and 5 were female. The instruments used in this study were tests, observations, interviews, and documentation, while the stages of data analysis in this study were data collection, data reduction, data presentation, and data interpretation. The research method used was Classroom Action Research (CAR). The implementation of learning followed the steps of the STAD type cooperative learning model assisted by ULTRASI media which consisted of two cycles, namely cycle I and cycle II. Each had four stages, namely planning, action, observation, and reflection. The minimum success criteria for each cycle were 75% of the completeness value in each cycle. The results of this study indicate that there was an increase in students' mathematics learning outcomes by implementing the STAD type cooperative learning model assisted by ULTRASI media on the basic arithmetic operations material on the topic of multiplication.